Ostatnia bitwa cesarza Juliana (24–26 lipca 363 r.) - Drabik, Adrian (Acta Universitatis Lodziensis. Folia Historica, 2014)
The article describes the battle between the armies of the Roman Empire and the Sasanid Persia, that took place in the second half of July 363. Emperor Julian prepared war against the Persia ruled by Shapur II. The campaign was carried out successfully until the imperial troops arrived at Ctesiphon. From this point forward, the Persians took advantage. The critical point was a stock of supplies of the Roman army, which became very short in June 363. Moreover, Julian ordered to reduce the amount of meals. Acquisition of stocks has become an important goal in Shapur II activities, because the destruction of part of the carts carrying food could lead to loss in the combat effectiveness of the Romans. During the battle of Samarra or Maranga (place of the battle is questionable), Sasanid troops managed to destroy a significant part of carts carrying supplies. Moreover, in the course of the battle many of the Roman officials and the Emperor Julian himself were killed. In the article the most important are the assumptions of the tactical side of the Shapur II’s plan, as well as the reaction of the Roman army in the difficult situation in the battle.